Relationship of Soft X–Ray caused from Solar Flares and Solar Energetic Particles at Maximum of Solar cycle 24 - Allawi, Habeeb. H. (University of Thi-Qar Journal of Science, 2014)
In the current research we studied solar flares and their associated interactions of solar energetic particles (SEPs) and productive relationship with X-rays generated in these blasts. Goal of this study is to detect the correlation between soft X-rays associated with SEPs. We take into consideration rely on soft X-ray emission associated with these particles as a reference guide to keep track of these particles. In this study we used three satellites research, a satellite (ERNE) which used to detect the intensity of solar energetic particles, and this satellite belonging to the U.S. space agency (NASA) in collaboration with the European Space Agency (ESA). The satellite research (GOES) to observe the solar X-rays flare, as well as satellite research (WIND WAVE) which has been used to detect solar radiation emissions, in addition to the data we have obtained from the International Space Station (SOHO) . The study was conducted for a full year (2012) at the maximum active of the solar cycle (24), where the analysis of all the data that have been obtained. The main objective of the research is to investigate the direct link between the solar soft X-ray and non- thermal solar particles reaching the ground. The study found that the soft X-rays class X resulting from solar flare be associated with solar particle stimulant SEPs generated and to the fact that radiation generated by a class X is composed at the same time in which it occurs explosions of coronal mass ejections CMEs.